Landscape as an affective and educational experience: differences in perception according to the urban-rural context - Alfonso-Torreño, Alberto; Pérez Sánchez, Javier; Giles Pérez, María Fernanda; Morote, Álvaro-Francisco (Anales de Geografía de la Universidad Complutense, 2026)
Landscape, understood as a social and emotional construct that integrates natural and cultural elements, represents a key educational resource for fostering environmental awareness and territorial identity. This study examines the perceptions and emotions elicited by urban and rural landscapes among Secondary Education students and prospective Primary Education teachers. Using a mixed-methods approach, a questionnaire was administered to 174 participants from different geographical contexts (rural, semi-rural, intermediate, and urban), combining inferential statistical analyses with qualitative analysis conducted in Atlas.ti. The results reveal a strong association between geographical context and landscape perception: rural students value nature, tranquillity, and biodiversity, whereas urban students emphasise services and leisure activities. Natural landscapes are predominantly associated with positive emotions and well-being, while urban landscapes generate more heterogeneous responses. Significant differences were also observed according to gender and educational stage in participants’ ability to distinguish and evaluate different types of landscape. These findings highlight the need for a landscape education that integrates reason and emotion in order to promote a critical environmental education that strengthens territorial identity.